ANALISIS TERHADAP FAKTOR PENYEBAB PERNIKAHAN WANITA HAMIL DI LUAR NIKAH DI DESA PANDANAN, KECAMATAN WONOSARI, KABUPATEN KLATEN TAHUN 2023 - Arifin, Usman Azis; Syamsuddin, S (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This research aims to answer the question of what are the causal factors regarding the marriage of pregnant women out of wedlock in Pandanan Village, Wonosari District, Klaten Regency, as well as how Islamic law analyzes the causal factors regarding the marriage of pregnant women in Pandanan Village, Wonosari District, Klaten Regency. The data sources in this research are community leaders. In collecting data, we used interview and document observation techniques to obtain data in the form of data about the causal factors regarding the marriage of pregnant women out of wedlock. Analysis of the data that has been collected in this research is using a qualitative descriptive method, which aims to analyze cases of pregnant women out of wedlock in Pandanan Village, Wonosari District, Klaten Regency. The results of this research explain that: The causes of pregnancy out of wedlock in Pandanan Village,Wonosari District, Klaten Regency are divided into several factors, namely first, the education system in this country does not form piety. Second, the media and the environment are driving teenagers' sexual desires to become increasingly uncontrolled. Third, family education has not become a family bulwark against immorality, including promiscuity. Fourth, society is indifferent to free association. Fifth, the state does not carry out its function as administrator and protector of the people.